Peta Riset Global Intervensi Keperawatan Berbasis Spiritual Pada Kecemasan Pra Operasi: Analisis Bibliometrik 2016-2025 - Ika Dwi Purwaningsih; Sutantri Sutantri; Titih Huriah (Universitas Malahayati Lampung, 2026)
ABSTRACT Preoperative anxiety has detrimental effects on psychological stability, postoperative pain, increased anesthetic requirements, and delayed postoperative recovery. Nursing practice plays a crucial role in preparing patients psychologically prior to surgery. Various nursing interventions have been developed to reduce preoperative anxiety and have been widely implemented across different countries through diverse research efforts. However, a structured mapping of global nursing research on preoperative anxiety remains limited. This study aimed to analyze the global research landscape of nursing studies on preoperative patient anxiety across countries using a bibliometric approach. This study employed a bibliometric research design using VOSviewer analysis. The keywords spiritual therapy, anxiety, preoperative, and pre operative were used to retrieve data from the Scopus database on February 17, 2026. A total of 569 articles were analyzed, demonstrating a consistent annual increase in research on preoperative anxiety. The highest number of publications originated from Turkey, the United States, and China. VOSviewer analysis revealed a shift in research trends toward non-pharmacological interventions. Six distinct clusters were identified, each representing specific research directions in nursing related to preoperative anxiety and visualized with different colors. All clusters were interconnected through the core keyword anxiety as the central node of the research network. Recent findings indicate that non-pharmacological interventions are increasingly developed and show substantial potential in nursing research, reflecting a growing interest in reducing preoperative anxiety through such approaches. Nursing research on non-pharmacological interventions, particularly those related to spirituality, has shown significant and increasing development. Spiritual interventions align with Kolcaba’s Comfort Theory, which conceptualizes patients holistically. Further research is warranted to advance the development of non-pharmacological, especially spiritually based, nursing interventions. Keywords: Bibliometrik, Spirituality, Anxiety, Preoperative. ABSTRAK Pendahuluan: kecemasan pasien pra operasi memiliki dampak buruk terhadap stabilitas psikologis, nyeri pasca operasi, peningkatan kebutuhan anestesi, dan proses pemulihan pasca operasi. Praktek keperawatan memiliki fokus penting dalam mempersiapkan psikologis pasien pra operasi. Berbagai intervensi keperawatan dikembangkan untuk menurunkan tingkat kecemasan pasien pra operasi. Intervensi tersebut banyak dilakukan di berbagai negara dalam berbagai riset. Namun, belum ada pemetaan secara terstruktur mengenai penelitian tersebut. Penelitian ini bertujuan untuk menganalisis peta riset global penelitian keperawatan tentang kecemasan pasien pra operasi dari berbagai negara menggunakan pendekatan bibliometrik. Penelitian ini menggunakan desain bibliometrik dan analisis vosviewer dengan kata kunci spiritual therapy, anxiety, preoperative dan pre operative berdasarkan data dari Scopus pada pencarian tanggal 17 Februari 2026. sebanyak 569 artikel dianalisis menunjukan peningkatan penelitian mengenai kecemasan pra operasi setiap tahunnya dengan publikasi terbanyak dari negara Turki, Amerika Serikat dan China. Analisis vosviewer menunjukan adanya pergeseran tren penelitian menggunakan intervensi nonfarmakologis. Dalam vosviewer terbentuk enam kluster yang memfokuskan arah penelitian keperawatan terkait kecemasan pasien pra operasi dengan warna yang berbeda dari setiap klusternya. Setiap kluster memiliki hubungan pada kata kunci inti yaitu anxiety sebagai pusat jaringan. Hasil penelitian terbaru menunjukkan intervensi non farmakologis semakin berkembang dan berpotensi besar dalam riset keperawatan. Hal ini menunjukan bahwa penurunan kecemasan pra operasi dengan terapi nonfarmakologis semakin diminati. Penelitian keperawatan mengenai intervensi keperawatan nonfarmokologis terutama spiritualitas mengalami perkembangan yang signifikan dan cenderung meningkat. Intervensi spiritual sesuai dengan teori kenyamanan Kolcaba yang menilai manusai secara menyeluruh. Perlu adanya penelitian lebih lanjut mengenai pengembangan intervensi nonfarmakologis terutama berbasis spiritual. Kata Kunci: Bibliometrik, Spirituality, Kecemasan, Pra Operasi.